Notorious : an It Girl novel - Von Ziegesar, Cecily (New York : Little, Brown, 2006)
Jenny Humphrey's escapades at the elite Waverly Academy in New York's horse country come to the attention of former campus queen Tinsley Carmichael as the two compete for the title of "It Girl."
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Wealth -- Fiction; Interpersonal relations -- Fiction; Conduct of life -- Fiction; Boarding school students -- Fiction; Teenage girls -- Fiction; New York (State) -- Fiction